ART INTERPRETATION OF IDEOLOGICAL MYTH IN CHANGING STARS OF MEZANTYUK «AS I RUNNING THE EMPIRE» - Ушневич, С. Е. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The study and understanding of literature for children first decades of the twenty-first century belongs to the priorities of contemporary literary and theoretical interpretative process. The phenomenon of children’s literature is interpreted as a narrative model of aesthetic communication through the prism-shaped plot structure and time-space. Literary Tale relatively young genre. It was a difficult path of development, transfer of folk tales - to fantastic f, lyrical miniatures and fairy tales-tetralolohiy. The writer proposes the concept worldcreation through the prism of Ukrainian mentality with respect to family values, the importance of images of mother and father.